2019
DOI: 10.1093/biolre/ioz208
|View full text |Cite
|
Sign up to set email alerts
|

Increased uterine artery blood flow in hypoxic murine pregnancy is not sufficient to prevent fetal growth restriction†

Abstract: Incomplete maternal vascular responses to pregnancy contribute to pregnancy complications including intrauterine growth restriction (IUGR) and preeclampsia. We aimed to characterize maternal vascular dysfunction in a murine model of fetal growth restriction as an approach toward identifying targetable pathways for improving pregnancy outcomes. We utilized a murine model of late-gestation hypoxia-induced IUGR that reduced E18.5 fetal weight by 34%. Contrary to our hypothesis, uterine artery blood flow as measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
0
13
0
2
Order By: Relevance
“…Further, as previously reported and discussed (Lane et al . 2019 b ), our model of hypoxia‐induced fetal growth restriction differs from human hypoxic pregnancy in that the mice have elevated uterine artery blood flow with hypoxia compared to normoxia. Although this model is still useful for identifying strategies for improving uterine artery blood flow, a hypoxia‐induced fetal growth restriction model with reduced uterine artery blood flow would be helpful for validating the present findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, as previously reported and discussed (Lane et al . 2019 b ), our model of hypoxia‐induced fetal growth restriction differs from human hypoxic pregnancy in that the mice have elevated uterine artery blood flow with hypoxia compared to normoxia. Although this model is still useful for identifying strategies for improving uterine artery blood flow, a hypoxia‐induced fetal growth restriction model with reduced uterine artery blood flow would be helpful for validating the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…2016; Lane et al . 2019 b ). Supporting an additional mechanism for increasing uteroplacental blood flow, AMPK‐activating drugs have also been shown to have pro‐angiogenic effects in the uteroplacental unit (Bourque et al .…”
Section: Introductionmentioning
confidence: 99%
“…Calculated blood flow (mL/min*kg) yielded a coefficient of variation of ~10%, demonstrating technical precision ( Supplemental Fig. S1 ) [ 41 ]. First, we assessed baseline uterine and renal artery parameters for untreated ovariectomized CSE KO and WT animals.…”
Section: Resultsmentioning
confidence: 99%
“…Such variation suggests that differences among animal models, types of tissues, and the duration or magnitude of hypoxic exposure have dissimilar effects on AMPK activation. We recently reported that in vivo treatment with the AMPK activator, AICAR, prevented half of the hypoxia-elicited decrease in murine fetal growth [24], strongly implicating a role of AMPK in the regulation of fetal growth under hypoxic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in pregnant mice under hypoxic conditions revealed similar results as well. One report showed that hypoxia augmented AMPK phosphorylation in the placental labyrinthine zone [23], while a subsequent one showed the opposite effect in murine placental homogenates [24]. Such variation suggests that differences among animal models, types of tissues, and the duration or magnitude of hypoxic exposure have dissimilar effects on AMPK activation.…”
Section: Introductionmentioning
confidence: 99%